D-glucose Increases the Synthesis of Tissue-type Plasminogen Activator (t-PA) in Human Peritoneal Mesothelial Cells - Sitter, Thomas; Mandl-Weber, Sonja; Wörnle, Markus; Haslinger, Bettina; Goedde, Martin; Kooistra, Teake (Thrombosis and Haemostasis, 1999)
Physical and chemical irritation of the peritoneum through glucose-based hyperosmolar dialysis solutions results in a nonbacterial serositis with fibrinous exudation. Thereby, human peritoneal mesothelial cells (HMC) play an important role in maintaining the balance between the peritoneal generation and degradation of fibrin by expressing the fibrinolytic enzyme tissue-type plasminogen activator (t-PA) as well as the specific plasminogen activator inhibitor-1 (PAI-1). In this study, we analyzed the effect of D-glucose and metabolically inert monosaccharides on the synthesis of t-PA and PAI-1 in cultured HMC.Incubation of HMC with D-glucose or the metabolically inert monosaccharides mannitol and L-glucose (5-90 mM) resulted in a time- and concentration-dependent increase in t-PA mRNA expression and antigen secretion without affecting PAI-1 synthesis. A similar effect was evident when HMC were first exposed sequentially to pooled spent peritoneal dialysis effluent for up to 4 hours, and subsequently incubated for 20 hours in control medium. The stimulating effect of high D-glucose on t-PA expression in HMC was prevented by treating the cells with different protein kinase C (PKC) inhibitors (Ro 31-8220, Gö 6976), but could not be mimicked by the PKC-activating phorbol ester PMA, indicating that this effect of high glucose is dependent on PKC activity, but not mediated through PKC activation. Also, using specific inhibitors (PD 98059, SB 203580) and activators (PMA, anisomycin, IL-1α) of the major routes of the mitogen-activated protein kinases (MAPKs) cascade, we found no evidence for a role of this cascade in regulating t-PA expression in HMC.We conclude that hyperosmolarity induces t-PA (but not PAI-1) in HMC via a regulatory mechanism that requires active PKC, but that does not involve a major pathway in the MAPK cascade.